Cations in a Molecular Funnel: Vibrational Spectroscopy of Isolated Cyclodextrin Complexes with Alkali Metals. Issue 2 (13th December 2012) - Gámez, Francisco; Hurtado, Paola; Hortal, Ana R.; Martínez‐Haya, Bruno; Berden, Giel; Oomens, Jos
Abstract The benchmark inclusion complexes formed by α‐cyclodextrin (αCD) with alkali‐metal cations are investigated under isolated conditions in the gas phase. The relative αCD‐M+ (M=Li+, Na+, K+, Cs+) binding affinities and the structure of the complexes are determined from a combination of mass spectrometry, infrared action spectroscopy and quantum chemical computations. Solvent‐free laser desorption measurements reveal a trend of decreasing stability of the isolated complexes with increasing size of the cation guest. The experimental infrared spectra are qualitatively similar for the complexes with the four cations investigated, and are consistent with the binding of the cation within the primary face of the cyclodextrin, as predicted by the quantum computations (B3LYP/6‐31+G*). The inclusion of the quantum‐chemical cation disrupts the C6 symmetry of the free cyclodextrin to provide the optimum coordination of the cations with the ‐CH2OH groups in C1, C2 or C3 symmetry arrangements that are determined by the size of the cation.